Protocol for an effectiveness- implementation hybrid trial to assess the effectiveness and cost-effectiveness of an m-health intervention to decrease the consumption of discretionary foods packed in school lunchboxes: the ‘SWAP IT’ trial - Rachel Sutherland (BMC Public Health, 2019)
Abstract Background At a population level, small reductions in energy intake have the potential to contribute to a reduction in the prevalence of childhood obesity. In many school systems, there is the potential to achieve a reduction in energy intake through modest improvements in foods packed in children’s school lunchboxes. This study will assess the effectiveness and cost-effectiveness of a multi-component intervention that uses an existing school-based communication application to reduce the kilojoule content from discretionary foods and drinks consumed by children from school lunchboxes whilst at school. Methods A Type I hybrid effectiveness-implementation cluster randomised controlled trial will be conducted in up to 36 primary schools in the Hunter New England, Central Coast and Mid North Coast regions of New South Wales, Australia. Designed using the Behaviour Change Wheel, schools will be randomly allocated to receive either a 5-month (1.5 school terms) multi-component intervention that includes: 1) school lunchbox nutrition guidelines; 2) curriculum lessons; 3) information pushed to parents via an existing school-based communication application and 4) additional parent resources to address common barriers to packing healthy lunchboxes or a control arm (standard school practices). The study will assess both child level dietary outcomes and school-level implementation outcomes. The primary trial outcome, mean energy (kJ) content of discretionary lunchbox foods packed in children’s lunchboxes, will be assessed at baseline and immediately post intervention (5 months or 1.5 school terms). Analyses will be performed using intention to treat principles, assessing differences between groups via hierarchical linear regression models. Discussion This study will be the first fully powered randomised controlled trial internationally to examine the impact of an m-health intervention to reduce the mean energy from discretionary food and drinks packed in the school lunchbox. The intervention has been designed with scalability in mind and will address an important evidence gap which, if shown to be effective, has the potential to be applied at a population level. Trial registration Australian Clinical Trials Registry ACTRN:12618001731280 registered on 17/10/2018. Protocol Version 1.